Reflections on Israel Studies as an Academic Discipline after 28 years of Editing the Israel Studies Journal. - Aridan, Natan (Israel Studies)
This article provides a comprehensive overview of the development and challenges of Israel Studies as an academic discipline and the journal *Israel Studies*, affiliated with Ben-Gurion University of the Negev. Israel Studies is a multidisciplinary field and journal that examines Israeli society, culture, history, and politics, including the diverse groups within Israel and its diaspora, with an emphasis on the State of Israel. The article discusses debates over the field’s distinctiveness from Jewish Studies and Middle East Studies, the establishment of Israel Studies centers in North America and Israel, and the political and academic controversies surrounding the discipline, including issues related to the Boycott, Divestment, Sanctions (BDS) movement. It also highlights the journal’s commitment to rigorous peer review, intellectual diversity, and addressing contentious topics without advocacy, contributing to the global expansion and recognition of Israel Studies scholarship.